Statistično spremljanje razvoja mehaniziranosti gospodarskih družb v obdobju od leta 1966 do leta 2002 - Resman, Simon (Zbornik gozdarstva in lesarstva, 2005)
Statistical monitoring of technical efficiency of various forestry companies was analysed. The monitoring was in view of data published in the past dividedinto three periods: 1966-1985, 1986-1992 and post-1994 period. Some relevant data for the 1966-2002 period were gathered, indicating a fairly highforestry development level. The data on forest density, volume of felled wood, number of people employed, technical efficiency, fuel consumption duringthe forest work, and on building of forest roads were studied. The situation as far as forest enterprises' operational efficiency is concerned isimproving, although it still greatly lags behind the equipment and efficiency in the more developed countries. Since 1994, a regular annual data monitoring has been taking care by the Statistical Office of the Republic of Slovenia. In order to get as precise data as possible, the required particulars should be defined more accurately and the given questionnaires demanded to be returned more consistently, considering that an unfilled or unreturned questionnaire means a fairly great gap in the joint data analyses. However, as comparisons between respondents are no longer possible due to the Law on data protection, the companies' interest in this kind of research is fairly small.
Keywords: gozdno gospodarstvo; pridobivanje lesa; Slovenia; Slovenija; statistični podatki; tehnična opremljenost